Risk factors for Epstein-Barr virus-related post-transplant lymphoproliferative disease after allogeneic hematopoietic stem cell transplantation - Uhlin, Michael (Ferrata Storti Foundation, 2014)
Allogeneic hematopoietic stem cell transplantation is a successful treatment for hematologic malignancies and a variety of genetic and metabolic disorders. In the period following stem cell transplantation, the immune-compromised milieu allows opportunistic pathogens to thrive. Epstein-Barr virus-associated post-transplant lymphoproliferative disease can be a life-threatening complication for transplanted patients because of suppressed T-cell-mediated immunity. We analyzed possible risk factors associated with post-transplant lymphoproliferative disease in a cohort of over 1,000 patients. The incidence of post-transplant lymphoproliferative disease was 4%. Significant risk factors identified by multivariate analysis were: human leukocyte antigen-mismatch (P<0.001), serological Epstein-Barr virus mismatch recipient−/donor+ (P<0.001), use of reduced intensity conditioning (P=0.002), acute graft-versus-host disease grade II to IV (P=0.006), pre-transplant splenectomy (P=0.008) and infusion of mesenchymal stromal cells (P=0.015). The risk of post-transplant lymphoproliferative disease has increased in more recent years, from less than 2% before 1998 to more than 6% after 2011. Additionally, we show that long-term survival of patients with post-transplant lymphoproliferative disease is poor despite initial successful treatment. The 3-year survival rate among the 40 patients with post-transplant lymphoproliferative disease was 20% as opposed to 62% among patients without post-transplant lymphoproliferative disease (P<0.001). The study identifies patients at risk of post-transplant lymphoproliferative disease after transplantation in need of pre-emptive measures.